Pengembangan Sistem Informasi Laboratorium Untuk Meningkatkan Efisiensi dan Akurasi - Modestus La’a; Vip Pramarta (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2023)
The development of laboratory information systems has become a primary focus in efforts to enhance efficiency and accuracy in laboratory operations. This article discusses the need for system development and evaluates the existing systems, which may be inefficient or inaccurate. Through analysis, it is found that repetitive manual tasks, such as data entry, inventory tracking, and report generation, result in time wastage and increased human errors. Furthermore, fragmented and non-integrated systems in laboratories impede smooth information flow, reduce operational efficiency, and increase the risk of errors. Reporting is also limited and time-consuming. Based on this background, this journal aims to develop an efficient and accurate laboratory information system. The development methodology includes user requirement gathering, needs analysis, system design, development, and implementation. In the development process, tools and technologies such as RFID are employed to improve operational efficiency and data accuracy. Integration among system components is also enhanced to facilitate smoother information flow. The evaluation results demonstrate significant benefits of the laboratory information system development. Manual tasks can be reduced, operational efficiency is enhanced, and the risk of human errors is decreased. Tracking and monitoring become easier, while reporting becomes faster and more accurate. With the adoption of an integrated laboratory information system, laboratories can improve their efficiency and accuracy in operations. In conclusion, the development of a laboratory information system is a crucial step in enhancing efficiency and accuracy. Through appropriate approaches and the implementation of information technology, laboratories can reduce reliance on manual work, improve data accuracy, and facilitate smooth information flow. The implementation of an efficient laboratory information system will have a positive impact on productivity and service quality in laboratories.